Research on the application of the family constellations method of Bert Hellinger to clinical supervision - Gómez Gómez, Francisco (2005)
The empiric part of this investigation work includes the systemic intervention models and phenomenologic in the pattern of the family constellations, as well as the pattern of the social representations. The investigation consists on applying the method of the family constellations created by Bert Hellinger to the clinical supervision. For it, fourteen cases were studied, presented by the participant psychotherapists in the same one. The results give bill of the changes of beliefs, convictions and degrees of the participants’ satisfaction in the group dynamics. In definitive, the investigation picks up the changes in the social representations of the investigated psychotherapists, have more than enough its problems and labor relationships, as consequence of the application of the method of the family constellations.